Morphological and Pathological Variability in Midrib and Stalk Isolates of Colletotrichum falcatum, the Cause of Red Rot of Sugarcane in North India - kumar, Rakesh; Sharma, Bipen; Sandhu, S. K.; Biswas, S. K. (International Journal of Bio-resource and Stress Management, 2015)
Morphological, cultural and pathogenic variability of seven isolates of C. falcatum revealed that the average conidial size of midrib and stalk isolates varied from 23.0-27.5×5.7-7.0 µm and 26.8-35.0×7.6-8.0 µm respectively. Two midrib isolates namely MR-5 and MR-6 from CoJ 85 and one stalk isolate CF-06 from CoJ 85 were relatively fast growing with an average colony diameter in the range of 13.3-13.6 mm, 36.5-36.9 mm and 84.1-84.2 mm and 13.5-13.9, 38.5 and 84.9 after 3, 5 and 7 days of incubation, respectively. All the midrib isolates showed low and stalk isolates low, medium and high sporulation which ranged from 2.08 to 16.67×105/9 mm disc (low), 16.67 to 29.17×105/9 mm disc (medium) and 29.17 to 41.67×105/9 mm disc (high). On the basis of morphological characters, midrib isolates produced dark type and stalk isolates produced with light and dark type colony colour. Pathogenic variability in midrib and stalk isolates of C. falcatum was studied on fourteen host differentials. On the basis of reaction expressed by seven midrib red rot isolates were grouped into five pathotypes based on their virulence. Group I designated as MR Pb-1 from CoJ 85 (Isolate MR-5 and MR-6) was highly virulent and produced intermediate reaction on 6 differentials and stalk red rot isolates were grouped into four pathotypes based on their virulence. Group I designated as CF Pb-1 from CoJ 85 (Isolate MR-5 and MR-6) was highly virulent and produced susceptible reaction on 10 differentials. A positive correlation between virulence and rate of growth was observed.